Effects of Nanofilled Particle Forms and Dispersion Modes on Properties of Carbon-Based Energy Storage Composites - Jia Yu; Hui Li; Li Kong; Hongji Zhu; Qingshan Zhu; Haoqing Wang (Advances in Polymer Technology)
How to improve the thermal conductivity of phase change materials (PCMs) is always the key to thermal control technology. At present, the thermal conductivity of PCMs has two ways to improve: one is to fill the matrix with high thermal conductivity and the other is to fill nanoparticles. After combining the two methods, the choice of filled nano-SiO2, carbon nanotubes (CNTs), or graphene (GNPs) has different effects on the performance of carbon-based energy storage composites. Filling paraffin with foamed carbon increased the thermal conductivity of pure paraffin from 0.25 W/(m·K) to 8.3083 W/(m·K), an increase of 33.2 times. When the nanoparticle mass fraction is 5%, the enthalpy of GNP composites is 10 J·g-1 less than that of SiO2 composites. Under the same mass fraction, compared with the thermal conductivity enhancement effect of SiO2 composites, the thermal conductivity increase effects of CNTs and GNP composites are 6.7 and 15.8 times the thermal conductivity increase of SiO2 composites, respectively. The comparison of theoretical and experimental values shows that different nanoparticle forms and dispersion modes have different effects on the performance of carbon-based energy storage composites, among which GNPs have the greatest improvement in the thermal conductivity of carbon-based composites.